1995
DOI: 10.1002/arch.940300104
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of sex pheromone biosynthesis in the turnip moth, Agrotis segetum

Abstract: Pheromone production in the female turnip moth, Agrotis segetum, is under the control of a brain factor. This factor was demonstrated to be a proteinaceous substance termed pheromone biosynthesis activating neuropeptide-like substance (PBAN-like substance). The sex pheromone of Swedish A. segetum includes (d-5-decenyl acetate, (d-7-dodecenyl acetate, and (a-9-tetradecenyl acetate as major components. Decapitation of a female decreased pheromone production significantly. Pheromone production was restored by inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…Such hormonal cross-reactivity has been reported for several other lepidopteran species (Raina et al, 1987;Rafaeli and Soroker, 1989;Qiu and Cao, 1989;Gazit et al, 1992;Picimbon et al, 1995;Zhu et al, 1995). Interestingly, the level of pheromonotropic activity did not differ between intra-and inter-Br-SEG treatments, probably because both species are of similar size (Raina et al, 1987) and/or their brain factors are structurally very similar (Gazit et al, 1992).…”
Section: Discussionsupporting
confidence: 74%
“…Such hormonal cross-reactivity has been reported for several other lepidopteran species (Raina et al, 1987;Rafaeli and Soroker, 1989;Qiu and Cao, 1989;Gazit et al, 1992;Picimbon et al, 1995;Zhu et al, 1995). Interestingly, the level of pheromonotropic activity did not differ between intra-and inter-Br-SEG treatments, probably because both species are of similar size (Raina et al, 1987) and/or their brain factors are structurally very similar (Gazit et al, 1992).…”
Section: Discussionsupporting
confidence: 74%
“…The pheromonotropic activity in hemolymph in A. segetum was much lower than that in Br-SOG or VNC. Zhu et al (1995) did not find any pheromonotropic activity in hemolymph in the scotophase. In the present study, a low but significant pheromonotropic activity was detected in the hemolymph during the scotophase.…”
Section: May 2002mentioning
confidence: 70%
“…Furthermore, pheromonotropic activity was detected in both hemolymph and VNC at certain photoperiod in the present study. Zhu et al (1995) also showed that severing VNC had no effect on the PBAN-induced pheromone production by injecting Br-SOG homogenates into decapitated female turnip moths. However, neither Zhu et al (1995) nor the present study observed any significant pheromone production when isolated pheromone glands were incubated with PBAN.…”
Section: May 2002mentioning
confidence: 96%
See 1 more Smart Citation
“…Other experiments aimed at determining the role of the VNC on pheromone production involve injection of PBAN into whole females or incubation with PBAN of isolated abdomens either intact or devoid of the VNC and the TAG (Jacquin et al, 1994;Jurenka et al, 1991;Ramaswamy et al, 1995;Teal et al, 1989;Zhu et al, 1995). As indicated above, when the abdomen incubation bioassay was performed with S. littoralis, it became clear, in agreement with all cases previously described in other species, including M. brassicae (Jacquin et al, 1994;Jurenka et al, 1991;Teal et al, 1989;Zhu et al, 1995), that PBAN stimulated pheromone production in the absence of the VNC and the TAG.…”
Section: Discussionmentioning
confidence: 99%